Kontribusi Budaya Organisasi Islami dalam Upaya Meningkatkan Kinerja - Mohammad Mustari (Jurnal Iman dan Spiritualitas, 2022)
This paper discussed developing organizational culture in both government and private circles. This research is a literature review, by conducting a study of documents following the research topic. This study concludes that organizational culture in government and private institutions will develop if you apply a balanced concept between general organizational management and religious management, especially from an Islamic perspective. Islam as a religion is known for its concept of discipline and a combination of working earnestly and trusting. Especially in the current pandemic era, the idea of organizational culture by including Islam as a perspective is very suitable. Administrative culture management can be balanced and create quality workers and employees.